2002
DOI: 10.1146/annurev.ento.47.091201.145217
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Methyl Bromide Treatments for Stored-Product and Quarantine Insects

Abstract: Methyl bromide is used to control insects as a space fumigant in flour and feed mills and ship holds, as a product fumigant for some fruit and cereals, and for general quarantine purposes. Methyl bromide acts rapidly, controlling insects in less than 48 h in space fumigations, and it has a wide spectrum of activity, controlling not only insects but also nematodes and plant-pathogenic microbes. This chemical will be banned in 2005 in developed countries, except for exceptional quarantine purposes, because it de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
239
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(249 citation statements)
references
References 59 publications
1
239
0
9
Order By: Relevance
“…Efforts are being made to develop economical, safe, and environmentally friendly alternatives for the control of stored product insect pests. Chemicals such as carbonyl sulfide, sulfuryl fluoride, ozone, cyfluthrin, iodomethane, and nonchemical treatments including modified atmospheres, high pressure, heat/cold treatments, sanitation, radio frequency, long-wave energy and irradiation have been utilized (Desmarchelier et al, 1998;Johnson et al, 2000;Fields and White, 2002;Schneider et al, 2003;Aksoy et al, 2004;Cetinkaya et al, 2006). Several studies have demonstrated that applications of modified atmospheres (MA) and ozone are possible alternatives for methyl bromide against dried fruits pests including C. cautella (Soderstrom et al, 1984;Soderstrom et al, 1986;Navarro et al, 1993;Donahaye et al, 1994;Navarro et al, 1997;Donahaye et al, 1998;Navarro et al, 1998;Navarro et al, 2000, Husain et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts are being made to develop economical, safe, and environmentally friendly alternatives for the control of stored product insect pests. Chemicals such as carbonyl sulfide, sulfuryl fluoride, ozone, cyfluthrin, iodomethane, and nonchemical treatments including modified atmospheres, high pressure, heat/cold treatments, sanitation, radio frequency, long-wave energy and irradiation have been utilized (Desmarchelier et al, 1998;Johnson et al, 2000;Fields and White, 2002;Schneider et al, 2003;Aksoy et al, 2004;Cetinkaya et al, 2006). Several studies have demonstrated that applications of modified atmospheres (MA) and ozone are possible alternatives for methyl bromide against dried fruits pests including C. cautella (Soderstrom et al, 1984;Soderstrom et al, 1986;Navarro et al, 1993;Donahaye et al, 1994;Navarro et al, 1997;Donahaye et al, 1998;Navarro et al, 1998;Navarro et al, 2000, Husain et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, phytosanitary treatments are required to disinfest quarantine pests and insects in agricultural commodities. Methyl bromide gas is commonly used for phytosanitary treatment of agricultural commodities, including the apple and pear, owing to its wide spectrum of activity (Fields and White, 2002;Hallman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of methyl bromide is in the process of being phased out, since it was listed as one of several substances that contribute to the depletion of ozone in the atmosphere in the Montreal Protocol (Fields and White, 2002). Although the United States dry-cured ham industry can use existing stocks of methyl bromide, no additional methyl bromide can be produced at this time (EPA, 2017).…”
mentioning
confidence: 99%
“…Alternatives that have been tested include chemical alternatives (Fields and White, 2002), food-safe compounds , the use of hot or cold temperature , and controlled atmosphere (Hasan et al, 2016). Sulfuryl fluoride was effective at controlling the adult stage of mites but was not effective at a concentration 3 times greater than the EPA label rate when applied at room temperature (Phillips et al, 2008).…”
mentioning
confidence: 99%